University setting and infrastructure for the people’s well-being: Universidad de Guadalajara in the face of the pandemic - Ricardo Villanueva Lomelí; Paola Lyccette Corona Gutiérrez; Rafael Serrano González (Universitas Diponegoro, 2022)
From the beginning of the COVID-19 pandemic in Mexico, the University of Guadalajara (UdeG) placed its infrastructure, —particularly schools, laboratories, research centers and institutes, and departments related to the areas of health and human resources— at the service of civil authorities and the population in general. Before any other public university in Mexico, UdeG implemented and published measures to prevent COVID-19 infections, which began with the suspension of public meetings and face-to-face activities, and the installation of a Health Situation Room, and which continued with the Enabling of the Active COVID-19 Detection System, the reconversion of the Civil Hospitals of Guadalajara, until reaching the Design of the Vaccination Plan, to name a few. The objective of this article is to describe how actions related to the management of the university environment and infrastructure not only put the largest state public university in the country at people’s service as never before, but also about how we have been forced to reconceptualize the mission and vision of higher education based on the needs identified during the pandemic, from a humanistic, integrative, unitary, global and interdisciplinary perspective.Keyword: COVID-19, universities, setting and infrastructure, health sciences, innovation